PENGARUH PROGRAM SEHARI BERBAHASA JAWA TERHADAP KETERAMPILAN BERBICARA BAHASA JAWA KRAMA SISWA MI AL JABBAR SUMBERAGUNG DANDER BOJONEGORO - Zumrotus Sa’diyah; Siti Nur Laili Febriyanti (Universitas Islam Lamongan, 2019)
Javanese language is the language most widely used by Indonesian people after Indonesian, because the Javanese population is very large, spread throughout Indonesia. But along with the development of the Java language, especially Javanese language krama almost extinct caused by the younger generation lacking appreciation of the Javanese language as their regional language. In this study, researchers will analyze a Javanese language learning program that is a day of Javanese language conducted by MI Al Jabbar with a focus on implementation, manners of language skills, and the effect of the program on students' karmic speaking skills. The results of this study indicate that the Javanese language program runs very well with an average score of 81.4 students. While the effect of a day program in Javanese language with students' language skills occupying the value of the linear regression equation was obtained Y = 25.4 + 1.331X with the regression significance test showing F *> F and by testing the correlation coefficient of r = 0.438 obtained t = 2.497 which stated the influence positive between the two variables. And with a significance level of 0.05 obtained t (0.05) (33) <t arithmetic. It can be concluded that there is an influence of a sebaja program (a day in Javanese language) on the skills of speaking Javanese Krama in Al-Jabbar MI Sumberagung Dander Bojonegoro